Development, Validation of LC-MS/MS Method and Determination of Pharmacokinetic Parameters of the Stroke Neuroprotectant Neurounina-1 in Beagle Dog Plasma After Intravenous Administration - Severino, Beatrice; Corvino, Angela; Fiorino, Ferdinando; Frecentese, Francesco; Perissutti, Elisa; Caliendo, Giuseppe; Santagada, Vincenzo; Magli, Elisa; Molinaro, Pasquale; Pignataro, Giuseppe; Annunziato, Lucio; Antunes, Natalícia J.; et al. (Frontiers in Pharmacology, 2019)
Neurounina-1 (chemical name: 7-nitro-5-phenyl-1-(pyrrolidin-1-ylmethyl)-1H-benzo[e][1,4]diazepin-2(3H)-one)is a new compound provided with relevant neuroprotective effect during stroke and in neonatal hypoxia by increasing the Na+/Ca2+ exchanger (NCX) isoforms NCX1 and NCX2 activity. This study shows for the first time, the development and validation of a sensitive and selective method for analysis of neurounina-1 in beagle dog plasma by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS). The sample preparation consisted of extraction of the analyte and the internal standard (ropivacaine) from plasma (50 µL) by liquid-liquid extraction using acetonitrile (100 µL). The selected reaction monitoring mode of the positive ion was performed and the precursor to the product ion transitions of m/z 365˃83 and m/z 275˃126 were used to measure the derivative of neurounina-1 and ropivacaine. The chromatographic separation was achieved using a Phenomenex C18 Luna (150 mm x 4.6 mm x 5 µm) analytical column with an isocratic mobile phase composed of methanol/acetonitrile/water (50/40/10, v/v/v) + 0.1% formic acid + 1 M ammonium formate. The method was linear over a concentration range of 1–500 ng/mL. The method was applied to evaluate the pharmacokinetics of neurounina-1 after a single intravenous administration of three different doses (0.1 mg/kg, 0.3 mg/kg and 1 mg/kg) to beagle dogs (n=5). The mean AUC0-tlast values were 26.10, 115.81 and 257.28 ng*h/mL following intravenous administration of 0.1, 0.3 and 1 mg/kg, respectively. Linear pharmacokinetics was observed up to 1.0 mg/kg. The neurounina-1 was rapidly eliminated, with mean CL values of 46.24, 47.57 and 69.15 L/h, Vd of 130.31, 154.15 and 210.79 L and t1/2 of 2.14, 2.54 and 2.04 h after intravenous administration of 0.1, 0.3 and 1 mg/kg, respectively. This new analytical method allows the rapid determination of the neurounina-1, a new developed compound, able to exert a remarkable neuroprotective effect in the low nanomolar range.